Development and validation of teacher competency perception scale in Indonesia: The Rasch analysis - Suharsimi Arikunto; Wahyu Nanda Eka Saputra; Dewi Afra Khoirunnisa; Rezki Perdani Sawai (Universitas Ahmad Dahlan, 2023)
Teachers have a role in building a civilization that upholds values and norms. Students are the party that the teacher focuses on to be educated. Of course, they have perceptions of teacher competence. This study aims to develop and validate a scale of perceptions of teacher competency. The instrument consists of four aspects: pedagogic, professional, personality, and social. This study uses Rasch analysis to test the construct validity of the teacher's competency perception scale. The construct validity test involved 400 students. Data analysis using WINSTEPS Rasch Software provides information about respondents' quality and instruments, easy and difficult items for respondents to agree on, fit order items, and unidimensionality. The results of the application of Rasch analysis showed that the teacher's competency perception scale is good, precise, and has item conformity with the model. The teacher competency perception scale is a reliable and valid tool to measure students' level of peace accurately. This study discusses the implications and recommendations for further research for implementing learning that optimizes the four teacher competencies.